Aspek Hukum Peraktik Kedokteran Melakukan Tindakan Medis Yang Bukan Kewenangan Kompetensi Profesinya - Ricky Ricky (Universitas Islam Indonesia, 2020)
This research was conducted to determine the limits of doctors in carrying out medical actions that are beyond the authority of their professional competence. This study is based on data that there are still doctors who perform medical actions beond their authority. This is normative legal research that is supported by empirical data by collecting legal materials and interviews. This paper concludes that the doctor’s authority in performing medical practice is required to have a Registration Certificate (STR) and License to Practice (SIP), as regulated in Articles 29 and 36 of Law Number 29 of 2004 on Medical Practice. A doctor is not allowed to take medical action beyond their competence since they possess no certificate of competence that recognizes their study during the educational process as regulated in Article 69 paragraph (1) of Law Number 36 Year 2009 on Health, if they are unable to carry out an examination and treatment then they can carry out the referral process to doctors who have expertise as regulated in Article 27 letter (b) of Law Number 29 of 2004 on Medical Practice.